DISTRIBUTION OF PKS-I, PKS-II AND NRPS GENES IN 23 ACTINOBACTERIAL STRAINS SELECTED FROM SPONGES IN THE HA TIEN SEA, VIETNAM (Vietnam Journal of Agriculture and Environment, 2023)
Marine actinobacteria are the most economically and biotechnologically valuable prokaryotes receiving much attention for their capacities of antibiotics and enzyme inhibitors. A total of 198 endophytic actinomycetes was isolated from 44 sam ples of 5 different sponge species in Ha Tien Sea, Vietnam. Twenty - three actinobacterial isolates against at least two of the five tested bacteria with moderate to high resistance were selected and characterized by the genetic sequencing method. They were identified to be belonged to 4 families: Actinomycetaceae, Microbacteriaceae, Nocardiaceae, and Gordoniaceae. The difference of present rate of genes including PKS-I, PKS-II and NRPS gene, was found as follows: 16/23 strains (with 69.6%), 14/23 strains (with 67.8%), 11/23 strains (with 47.8%) respectively, three strains had three PKS-I, PKS-II and NRPS genes, especially Gordonia bronchialis HD2.5a strain (Gordoniaceae) was the best strain in the resistance with 4/5 human diseases microbes. These new cultures can be employed as bioactive resources against pathogens, particularly in relation to food - borne diseases and human health.